Qualitative research investigating the mental health care service gap in Chinese burn injury patients - Zhengjia Ren; PeiChao Zhang; HongTao Wang; Hongyan Wang (BMC, 2018)
Abstract Background Psychological disturbances are prevalent in people with burn injuries; however, psychological services are rarely accessiblepost-burn injury in China. The objective of this qualitative study was to explore and conceptualize the obstacles to delivering mental health care in burn injury patients. Methods The researchers used a grounded theory research approach to interview sixteen burn injury patients, five nurses, four rehabilitation therapists, five medical doctors, and eight caregivers regarding their experiences with current health care services and barriers. Results An explorative model was generated from the data, and the relationships among the categories were identified. People's beliefs, knowledge, socioeconomic status, cultural understanding of mental health, and social stigma appear to play key roles in the public health approach to post-burn health promotion and post-burn psychosocial interventions. Conclusion The model proposed in our research highlights the need to focus on the underlying social, economic, and cultural determinants of mental health care. The underlying social determinants of the mental health care gap that is responsible for the ill-prepared health care must be addressed.